THE ARTISTIC EMBODIMENT OF THE IMAGE OF ENGLAND IN THE «LETTERS TO ANOTHER ROOM» BY RAVIL BUKHARAYEV - R. Gaynutdinova, Alina; F. Galimullina, Alfiya; G. Galimullin, Foat; K. Kairzhanov, Abay (Gênero & Direito, 2019)
The problem of the writer’s self-identification, especially of such a multifaceted one as Ravil Bukharayev, is closely connected with one of the topical problems of modern literary criticism and cultural studies – the problem of the Other. Ravil Raisovich Bukharayev (1951 - 2012) – a Tatar poet, writer, philosopher who wrote in Russian, lived for more than 20 years in England. In his work he demonstrates a new cultural situation, the ability to seamlessly apprehend the universal art culture, literature and worldview ideas from ancient times to the present day at the same time preserving his national and religious identity. The poetry by R. R. Bukharayev has repeatedly become the object of scientific research while the philosophical prose by R. R. Bukharayev is still waiting for his researcher. This article represents the experience of a scientific study of the artistic world of RR Bukharayev’s prose based on the example of his novel Letters to Another Room [1]. The results of our study suggest the following conclusions: The novel by R. R. Bukharayev “Letters to Another Room” presents the perception of England through the Other’s vision of it. R. R. Bukharayev representing himself as the Other in relation to the English tradition upends the preconceived idea of the English “gentleman” as the only bearer of the English literary and cultural tradition. Irony and self-irony help the narrator to isolate himself from Englishness of the created text: 1)The image of England in the novel by R. R. Bukharayev is ambiguous: on the one hand, the narrator found a real House with a wonderful garden, a place of rest and creativity in it, on the other – the author is far from idealizing English society. He seeks maximum objectivity in the artistic presentation of the image of England in his novel. 2)A distinctive feature of R. R. Bukharayev’s narrative is an integration of Russian and English realities in the text, which is manifested in comparisons of English everyday realities with memories of Russian life. In the minds of the author the images and associations connected with English and Russian literature and culture organically coexist.